PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN ASET, LIKUIDITAS, DAN LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Amelya, Amelya; Dermawan, Elizabeth Sugiarto (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study was to analyze and obtain empirical evidence regarding the effect of firm size, asset growth, liquidity, and leverage on firm profitability. The sample selection in this study was carried out using purposive sampling method and obtained a total sample of 160 data from manufacturing companies listed on the IDX with a research period from 2017 to 2019. The type of data used in this study is secondary data obtained from the IDX’s official website and related company websites. The results showed that the firm size, asset growth and liquidity had a positive and significant effect on company profitability, while leverage had a positive and insignificant effect on company profitability.